Medicinal Plants and Forest Transformations in NW Pakistan: A preliminary synthesis - Adnan, Muhammad; Hölscher, Dirk (Ethnobotany Research and Applications, 2014)
In the Pakistani Himalaya, local people use medicinal plants for healthcare and income generation. Medicinal plants have historically been collected below the tree line from near natural old-growth forests. However, such forests have almost disappeared today. In addition to the few remaining degraded forest remnants, some areas have become subject to restorative land-use approaches including agroforestry, reforestation, and natural re-growth. We studied a number of such transformational forest areas with respect to the abundance of medicinal plants and their local market prices. Of the ten target species studied, Viola canescens Wall. was the most valuable with the highest density occurring under old-growth forest, whereas it was almost absent from heavily degraded forest. Curiously, in new forests, its density was nine times higher under natural re-growth forest plots than under reforestation or agroforestry plots. Over the past six years, Viola’s market value has increased 2.6 times more than the consumer price index, and the rising market costs of ten study species are strongly related to their densities in old-growth forest (r2 = 0.6, p < 001). We assume this is related to the decline of old-growth forests and the consequent effects on the supply and demand of medicinal plants. Moreover, our results indicate close similarity of medicinal plant flora between old-growth and natural re-growth forests (0.56 Jaccard index). In conclusion, forest restoration with an emphasis on natural re-growth is important to the recovery of medicinal plants in Northwest Pakistan. Awareness of this outcome among locals may help to promote acceptance of reforestation measures in the region.